Relationship between the architecture and function of ankle plantar flexors with Achilles tendon morphology in ballet dancers - Nunes, G. S.; Tessarin, B. M.; Silva, R. S.; Serrão, F. V. (Human Movement Science, 2019)
Achilles tendinopathy is the most frequent foot overuse injury in ballet dancers and knowledge of clinically modifiable factors related to tendon structure in a population at risk, such as ballet dancers, would be important for the development of preventive programs. Therefore, the present study aimed to assess relationships of gastrocnemius muscle architecture and ankle plantar flexors function with Achilles tendon morphology in ballet dancers. Fifty-four measures from 27 ballet dancers were collected. Tendon morphology (thickness, echogenicity, hypoechoic areas and neovascularisation) and muscle architecture (thickness, pennation angle and fascicle length) were evaluated using ultrasonography; ankle plantar flexors torque was evaluated using hand-held dynamometry, flexibility was evaluated in maximal weight-bearing ankle dorsiflexion position using inclinometer, and endurance was evaluated using the heel rise test. Ankle plantar flexors torque and medial gastrocnemius muscle architecture (thickness, pennation angle and fascicle length) are associated with Achilles tendon thickness in ballet dancers (r2 = 0.24, p = 0.008). Ankle plantar flexors torque and medial gastrocnemius muscle fascicle length are also associated with the echogenicity of the Achilles tendon (r2 = 0.13, p = 0.03). These findings call attention to the potential importance of ankle plantar flexors muscle force in healthy ballet dancers for the prevention of alterations in Achilles tendon structure.